INCREASING STUDENT'S COMPETENCE THROUGH GRAPHIC DESIGN TRAINING PROGRAM AT BALAI LATIHAN KERJA KARAWANG - Ulan Sari; Dayat Hidayat; Tika Santika (Empowerment : Jurnal Ilmiah Program Studi Pendidikan Luar Sekolah, 2021)
The problem and purpose  in this study is based on the process, supporting and inhibiting factors, as well as the results in increasing the competence of learning citizens through graphic design training programs. To be able to answer the above problems, researchers used qualitative methods, data collection techniques in the form of observation, interviews, and documentation. The results showed that the process of increasing the competence of learning citizens consisted of several factors, starting with the recruitment stage of prospective learning citizens carried out very strictly, the steps in increasing competence had been carried out properly, updating materials according to the times, teaching media and teaching methods that according to the needs of learning citizens, as well as an assessment system that is viewed from two sides, namely theory and practice. The supporting and inhibiting factors are the interest, motivation and self-confidence of the learning community, facilities and infrastructure, costs, learning environment, to the competence of the instructor, all of which have been able to run well. And the learning outcomes in this graphic design training program have been running effectively and producing graduates who are in accordance with the goals that have been set previously.Keywords : competence, graphic design training program